The Roles of Implicit Causality and Discourse Context in Pronoun Resolution - van den Hoven, Emiel; Ferstl, Evelyn C. (Frontiers in Communication, 2018)
Some interpersonal verbs show a bias in the proportion of times their subject and object arguments are rementioned in a sample of explanations for the eventuality the verb describes. This bias is known as the implicit causality bias. Several studies have shown that readers and listeners rapidly use the implicit causality bias during pronoun resolution. Whether listeners also rapidly incorporate relevant contextual information during pronoun resolution, is an open question. In the current paper, we report two visual world eye-tracking studies intended to answer this question. Participants listened to stories that included implicit causality verbs followed by a “because” clause with an ambiguous pronoun in its subject position. During the story, the participants looked at a screen on which potential referents of the ambiguous pronoun were displayed. In Experiment 1, a simple main effect of implicit causality bias on looks toward the character that was congruent with the bias was found among items in one of the two discourse conditions. Discourse context, however, only affected looks for a subset of verbs and in the opposite direction of what was hypothesized. In Experiment 2, no main effects of IC Bias or discourse context were found, but there was a marginally significant interaction which was not hypothesized. In both experiments, discourse context influenced looks only for a subset of verbs and never in the predicted direction. The results favor an account in which the influence of lexical semantics is, at least initially, stronger than the influence of world knowledge and discourse context. Additional exploratory analyses suggested that eye movements already reveal remention biases at an early point in the sentence, whereas the causal potency of the subject argument is predicted by looks starting from the onset of the causal connective.